Veistosten valmistus Suomessa: Kuvanveistotaiteen tekniikan ja materiaalien historiaa 1890 - 1920 - Tossavainen, Mari (Tekniikan Waiheita, 2015)
This article examines the making of Finnish sculpture and it aims to advance our understanding of the technical history of Finnish sculpture. Materiality is a basic element of sculpture, but it is only recently that materiality and technical dimensions of sculpture have become the focus in the studies of sculpture. Late 19th century and early 20th century sculpture is closely tied to a new appreciation for technologies, to bronzes and to development of Finnish bronze foundries. During this period, a range of new technical possibilities were introduced.Before the turn of the century, the Finns did not possess the technology to cast bronze sculpture in this country. Finnish sculptors had to rely on other European foundries that situated in e.g. Paris, the world capital of art and the one of the centers of bronze casting. However, there were some other businesses related to sculpture in Finland, i. e. stonemasons. Around 1900, bronze was seen more practical and durable for public monuments and smaller sculpture. Especially, sculptors were interested in lost-wax (or cire perdue) casting. Also, the Finnish sculptors did casting experiments. Emil Wikström, one of the Finnish pioneers of bronze casting, established a small foundry in his Visavuori studio in 1903. The first Finnish foundries were established in the 1910s. The article shows that the competition between Finnish bronze foundries was hard.